Forceful or persistent: Wow the ECB's new inflation target affects households' inflation expectations - Mathias Hoffmann; Emanuel Mönch; Lora Pavlova; Guido Schultefrankenfeld (Deutsche Bundesbank, 2023)
We study how households adjust their medium-term inflation expectations under the new ECB strategy. We find that survey respondents make little difference between the previous strategy of targeting inflation rates close to but below 2% and the new strategy with a symmetric 2% target. Yet, participants informed that the ECB might tolerate rates exceeding the target for some time, expect somewhat higher medium-term inflation. Respondents asked to assume inflation currently running below target place a significantly higher probability on outcomes above 2% in the medium term. Participants do not expect an undershooting when inflation is currently running above target.
Keywords: F33; E31; E32; 330; Monetary Policy Strategy; Household Inflation Expectations; Randomized Control Trial; Survey Data